The prevalence of the extensor digiti minimi tendon of the hand and its variants in humans - Yammine, Kaissar (2015)
The extensor digiti minimi (EDM) is frequently used in the case of an abduction deformity of the little finger. It is also considered as a main resource for tendon transfer. However, it shows many variations in the human hand, which include splitting into two or more slips and sending a slip to the fourth finger, named the extensor digiti minimi et quarti (EDMQ). The aim of this systematic review is to perform an evidence synthesis on the prevalence of the EDM and its variants. Twenty-six cadaveric studies met the inclusion criteria with a total of 2247 hands. Meta-analysis results yielded an overall pooled prevalence estimate (PPE) of the EDM of 99.7 % and PPEs of 11.5, 77.6, 7 and 0.6 % for the single-, double-, triple- and quadruple-slip EDM, respectively. For the single-slip EDM, the frequencies were such that Indians > Middle Eastern > Europeans > Japanese > North Americans. For the double-slip EDM, the frequencies were such that Japanese > North Americans = Europeans > Middle Eastern > Indians. No significance was found with regard to hand side. The true EDMQ prevalence was found to be at 7.3 %, whereas its crude prevalence was 8 %. This artilce offers reference values on the prevalence of the EDM and its variants, which are thought to be highly relevant to both anatomists and clinicians.